The jurisdictional control of the registration rating: verbal trial about the property registrar rating. A special reference to the award decree and the refusal for recording it (Acta Judicial Journal, 2018)
The rating function of the Registrar, as exclusive guarantor for deeds recording at Land Registry, is not absolute and unlimited. The Procedural Law regulates a specific procedure against the Registrar refusal before the Civil Court sustained henceforth by verbal legal steps. In the rating of judicial documents, the question must be solved in the frame of the Article 18 of the Mortgage Law and Article 100 of Regulation- The Registrar decision presents aspects of singular interest, which demands the attention of the matter related to its procedural requirements and others. Among them, we point out the recording refusal by the Property Registrar due to the consideration that the interpretative doctrine of article 671.1 of the LECiv, emanating from the Management Center, is out of application in the award decree issued by the Judicial Administration Counselor.
Keywords: Mortgage foreclosure, registration rating, registration, judicial review, oral proceedings, award decree, auction, bidders, usual residence.